Padrão de especialização do comércio internacional brasileiro: uma análise das vantagens comparativas - Andriotta, Amanda de Brito (Universidade Federal de São Carlos, 2015)
During the most recent decades the Brazilian foreign trade has shown significant changes regarding its pattern of trade specialization. These changes suggest that the country is undergoing into a process of exports reprimarization, caused mainly by the increase of the Chinese demand for commodities. The increase of the share of commodities in trade transactions between Brazil and the rest of the world has happened at the same time that manufactures have lost importance in the nations’ total trade. The new composition of the Brazilian foreign trade transactions indicates the country is following a new pattern in the international market. In addition, not only the country’s exports composition has changed over the last years, but we can also verify changes in the main exports destinations rank list. In this paper, our goal is to investigate the dynamics of changes in the Brazilian foreign trade transactions, focusing on exports, during the period of 1997 and 2003. We divided our analysis in different sectors, destination markets, and different periods to have a better understand of how changes happened. Our main hypothesis is that the reveled comparative advantages in international trade have led the country to the reprimarization process of its exports. Moreover, fewer sectors have shown high competitive levels over the last years, indicating a poor dynamics of Brazilian exports. In order to test our hypothesis, we first calculated revealed symmetric comparative advantages indexes, and then used Markov chains to calculate their probability distributions in different periods. We combined the two methodologies to identify the sectors and groups of technology where the country has higher competitiveness. We could also test for changes in exports composition, identifying which were the sectors and technology groups with higher trade competitiveness, in each period. Our results show that Brazil has been using its comparative advantages in the international trade, and its exports are becoming more dependent of commodities, since this is the group of products with higher revealed comparative advantages index. We also found a general loss of competitiveness in the non-commodity sectors during the analyzed period, which clearly shows that the country is facing a process of export reprimarization. The analysis of trade regarding different groups of countries shows that, even though with different intensities, commodity exports are becoming more relevant to all exports destinations (BRICS, European Union, MERCOSUL, and NAFTA), and it has happened more intensively during the third reporting period (2007- 2011). In addition, we also found that there is an indication that, in the future (ceteris paribus), there will be a possible convergence of exports in sectors with lower levels of comparative advantage. Our findings indicate that Brazil has been losing competitiveness in international trade, even with those products that the country has more comparative advantages in trade.
Pattem of specialization of Brazil's international trade: an analysis of comparative advantages"
Keywords: Comércio internacional; International trade; Vantagem comparativa (Comércio); Comparative advantage (International trade); Primarização; Primarization; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INTERNACIONAL::RELACOES DO COMERCIO; POLITICA COMERCIAL; INTEGRACAO ECONOMICA